Urban livability index assessment based on land-use changes in an Indian medium-sized city (Raiganj). Issue 25 (13th December 2022) - Basu, Tirthankar; Das, Arijit; Pereira, Paulo
Abstract: Improvement of a city's liveability, especially in developing countries, is increasingly viewed as a way to enhance city dwellers' quality of life. This study applied remote sensing and GIS-based techniques to assess urban livability conditions based on the World Health Organization guidelines. For this, 21 fine-grained spatial indicators were selected, and a geographically weighted principal component analysis was applied to evaluate the spatial pattern of urban livability in Raiganj. The results showed that the city's central and eastern part had a livability index score over 0.75 (5.31 km 2 area) appeared as the most livable. The southwestern part of the city was the least livable. Finally, the predicted Land Use Land Cover for 2025 in Raiganj based on the Multilayer Perceptron Neural Network-Markov Chain showed that the city (+19.50%) will expand mainly in the eastern direction at the expense of green and blue spaces.